Antimicrobial resistance during the COVID-19 pandemic: the missing patient perspective. Issue 1 (22nd March 2021) - Dahal, Deepa; Sundar, Swarna; Kullar, Ravina; Milevska-Kostova, Neda; Dindial, Karen
Abstract: While the use of antibiotics for secondary infections in COVID-19 has been described in scientific literature and guidelines have been issued for their appropriate use, the importance of listening to patients in a systematic manner has often been overlooked. To highlight this issue, we spoke with patients about their experiences with antibiotics as treatment for COVID-19 and their understanding of antimicrobial resistance (AMR). We found that there is a general lack of awareness of the risks of AMR, and even when patients are knowledgeable, fear of COVID-19 and pressure from healthcare providers often override considerations for appropriate use. We present case examples of three patients' experiences and provide recommendations for health systems, healthcare providers, and patients or caregivers on actions they can each take to reduce the risk of AMR during and beyond the COVID-19 pandemic. We also share ways that the patient community can be empowered to provide their voices to decision-making on both COVID-19 treatment protocols and prescriptions of antibiotics.